Wrist Circumference as a Novel Predictor of Coronary Artery Disease and Metabolic Syndrome - Mondal, Palash; Basu, Subrata; Saha, Manish; Das, Krishanko (Nepalese Medical Journal, 2024)
Introduction: Wrist circumference is a good predictor of obesity and insulin resistance. Wrist circumference may be considered as an indirect determinant of hyperinsulinemia and insulin resistance. The present study aimed to assess wrist circumference as an alternative tool for differentiating patients with coronary artery disease and metabolic syndrome from those without coronary artery disease and metabolic syndrome. Materials and Methods: The study was conducted on patients ≥ 30 years old undergoing coronary angiography following acute coronary syndrome or for evaluation of coronary artery disease. Results: Diabetic, hypertensive, and obese patients had more wrist circumference. High TG, low HDL levels were associated with higher wrist circumference (p=0.005). Wrist circumference was positively correlated with waist-hip ratio (p<0.001). Patients with Metabolic Syndrome have a mean Wrist circumference of 16.54 whereas patients without Metabolic Syndrome have a mean wrist circumference of 15.89(p<0.001). Coronary artery disease patients had higher mean wrist circumference than non-coronary artery disease patients (16.59 vs 15.9) (p<0.001). Triple-vessel disease patients have higher wrist circumference than double-vessel-disease patients; Doublevessel- disease patients have higher wrist circumference than single-vessel disease (p<0.001). Multivariate logistic model shows the main predictors for coronary artery disease are male sex, smoking, high BMI, low HDL, and wrist circumference. Conclusion: Measurement of Wrist circumference can serve as an easy anthropometric marker to identify individuals at risk of cardio-metabolic disorder, and predict the severity of Coronary Artery Disease can be used in large epidemiological studies.